A Study of Self-help Intervention System for Social Anxiety in Vitiligo Based on Cognitive Behavioral Therapy - Yin, Tong (Transactions on Computer Science and Intelligent Systems Research, 2024)
Vitiligo is a common depigmented skin disease. Changes in appearance and unstable treatment outcomes have a negative impact on the physical and mental health of patients. Not only can it cause psychological problems such as social anxiety and depression, but it can also affect the effectiveness of disease treatment. Aim of the study: In order to help vitiligo patients reduce social anxiety and improve the applicability and practicality of psychotherapy, this article proposes a self-help intervention system based on cognitive-behavioral therapy (CBT) to help vitiligo patients establish correct cognitive and social behavior patterns. Method: Firstly, the psychological characteristics and existing treatment methods of vitiligo patients were analyzed. Secondly, the feasibility of CBT in human-computer interaction applications was explored. Negative cognition, social avoidance, and constructing psychological models for vitiligo patients have been comprehensively designed. Finally, summarize the information framework and core functions of the self-help intervention system. Results: An app as a carrier establishes a psychological intervention system that combines the patient’s own characteristics, including three main modules: cognitive training, social simulation, and psychological evaluation. Conclusion: The self-help intervention form of Internet CBT has innovated the method of psychotherapy for vitiligo, providing effective and cost-effective psychological treatment options.